Local stellar formation history from the 40 pc white dwarf sample. Issue 2 (5th April 2023) - Cukanovaite, E; Tremblay, P-E; Toonen, S; Temmink, K D; Manser, Christopher J; O'Brien, M W; McCleery, J
ABSTRACT: We derive the local stellar formation history from the Gaia -defined 40 pc white dwarf sample. This is currently the largest volume-complete sample of white dwarfs for which spectroscopy is available, allowing for classification of the chemical abundances at the photosphere, and subsequently accurate determination of the atmospheric parameters. We create a population synthesis model and show that a uniform stellar formation history for the last ≈10.5 Gyr provides a satisfactory fit to the observed distribution of absolute Gaia G magnitudes. To test the robustness of our derivation, we vary various assumptions in the population synthesis model, including the initial mass function, initial-to-final mass relation, kinematic evolution, binary fraction, and white dwarf cooling time-scales. From these tests, we conclude that the assumptions in our model have an insignificant effect on the derived relative stellar formation rate as a function of look-back time. However, the onset of stellar formation (age of Galactic disc) is sensitive to a variety of input parameters including the white dwarf cooling models. Our derived stellar formation history gives a much better fit to the absolute Gaia G magnitudes than most previous studies.